Micropartículas de poli (ácido láctico)/ poloxâmero obtidas por spray drying para liberação modificada de metotrexatro - Oliveira, Edilene Gadelha de (2014)
New drug delivery systems have been used to increase chemotherapy efficacy due the possible drug resistance of cancer cells. Poly (lactic acid) (PLA) microparticles are able to reduce toxicity and prolong methotrexate (MTX) release. In addition, the use of PLA/poloxamer polymer blends can improve drug release due to changes in the interaction of particles with biological surfaces. The aim of this study was developing spray dried biodegradable MTX-loaded microparticles and evaluate PLA interactions with different kinds of Pluronic® (PLUF127 and PLUF68) in order to modulate drug release. The variables included different drug:polymer (1:10, 1:4.5, 1:3) and polymer:copolymer ratios (25:75, 50:50, 75:25). The precision and accuracy of spray drying method was confirmed assessing drug loading into particles (75.0- 101.3%). The MTX/PLA microparticles showed spherical shape with an apparently smooth surface, which was dependent on the PLU ratio used into blends particles. XRD and thermal analysis demonstrated that the drug was homogeneously dispersed into polymer matrix, whereas the miscibility among components was dependent on the used polymer:copolymer ratio. No new drug- polymer bond was identified by FTIR analysis. The in vitro performance of MTX-loaded PLA microparticles demonstrated an extended-release profile fitted using Korsmeyer- Peppas kinetic model. The PLU accelerated drug release rate possible due PLU leached in the matrix. Nevertheless, drug release studies carried out in cell culture demonstrated the ability of PLU modulating drug release from blend microparticles. This effect was confirmed by cytotoxicity observed according to the amount of drug released as a function of time. Thus, studied PLU was able to improve the performance of spray dried MTX-loaded PLA microparticles, which can be successfully used as carries for modulated drug delivery with potential in vivo application